Soybean production in SEALBA: inoculation, co-inoculation, and starter nitrogen fertilization (Acta Scientiarum. Agronomy, 2024)
The grain production area in the Brazilian agricultural region known as SEALBA, especially in Alagoas State, has seen significant growth in recent years. This study aims to contribute to sustainable regional development by evaluating the effects of inoculation, co-inoculation, and the application of starter mineral nitrogen (N), either individually or in combination, on soybean growth and yield. Eight field experiments were conducted from 2018 to 2021 in two municipalities within Alagoas, covering soybean cultivation areas ranging from the first to the fourth year. The experiments followed a randomized complete block design with four replications, employing a factorial arrangement of treatments. The first factor encompassed five levels related to inoculation technologies and N management: 1) Inoculation with Bradyrhizobium; 2) Inoculation with Bradyrhizobium combined with N basal fertilization; 3) Co-inoculation of Bradyrhizobium + Azospirillum; 4) Co-inoculation of Bradyrhizobium + Azospirillum + N fertilization at the base; and 5) Control treatment without microbiological inputs or nitrogen fertilizers. The second factor involved the evaluation of different soybean cultivars, with two materials assessed in 2018 and three cultivars in 2019, 2020, and 2021. Results demonstrated that seed inoculation with Bradyrhizobium led to increased soybean grain yield in first-year cultivation areas. However, N basal fertilization, commonly known as starter fertilization, did not result in yield improvements compared to the use of microbiological inputs alone. Soybean cultivars BRS 9383 IPRO and FTR 3191 IPRO exhibited greater responsiveness to seed inoculation with Bradyrhizobium.